A stratified randomized response model for sensitive characteristics using the negative hypergeometric distribution. Issue 6 (19th March 2017) - Tarray, Tanveer A.; Singh, Housila P.
ABSTRACT: Taking clue from the pioneer work of Singh and Sedory (2013 ), we have suggested a new stratified randomized response (RR) model. The properties of the suggested stratified RR model have been studied under proportional and "Neyman" allocations. The study has been also carried out in the presence of crude prior estimates. Numerical illustrations are also given in support of the present study.